2014
DOI: 10.1007/s12613-014-0984-8
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of austenite grain growth behavior in the simulated coarse-grained heat-affected zone of Ti-microalloyed steels

Abstract: Abstract:The austenite grain growth behavior in a simulated coarse-grained heat-affected zone during thermal cycling was investigated via in situ observation. Austenite grains nucleated at ferrite grain boundaries and then grew in different directions through movement of grain boundaries into the ferrite phase. Subsequently, the adjacent austenite grains impinged against each other during the α→γ transformation. After the α→γ transformation, austenite grains coarsened via the coalescence of small grains and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…As the time progresses, the grain impinges against each other and gradually covers all the surface of specimen, implying that the α → γ transformation completes. This phenomenon has been revealed in our previous work . With time passing, the small austenite grains continue to grow slowly.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As the time progresses, the grain impinges against each other and gradually covers all the surface of specimen, implying that the α → γ transformation completes. This phenomenon has been revealed in our previous work . With time passing, the small austenite grains continue to grow slowly.…”
Section: Resultssupporting
confidence: 74%
“…The specimens were heated at a rate of 5 °C s −1 , then isothermally held at 1350 °C for 150 s, and immediately cooled at a rate of 5 °C s −1 . It should be noted that the heating and cooling rates (±5 °C s −1 ) are designed to be slower than that of actual thermal cycle with a high heat input for the observation of the grain boundary migration and acicular ferrite transformation at high/intermediate temperature during the simulated welding process . In addition, the difference in temperature between the top surface of specimen and the bottom of crucible is about 10–15 °C during the heat treatment .…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, in situ observation with high-temperature laser scanning confocal microscopy (HT-LSCM) has been utilized extensively to investigate the behavior of austenite grain growth during the thermal cycle of HAZ [25,26]. Wan et al [27] found that the growth process of austenite grains in Ti-micro-alloyed steel was a continuous process during heating, isothermal holding, and cooling in the simulated HAZ thermal cycling. Zhu et al [28] reported that the austenite grain size of steel with Mg deoxidation could hold the fine-grained structure after 1400 • C heating for 300 s. This inhibition of austenite grain growth was mainly attributed to the formation of pinning particles after the addition of Mg, resulting in the improvement of HAZ toughness [23].…”
Section: Introductionmentioning
confidence: 99%
“…5 It has been reported that acicular ferrite laths or plates partitioned large prior austenite grains into many finer and separate regions consisting of fine grained mixed microstructure with a small proportion of acicular ferrite grains embedded in fine bainite plate packets. [3][4][5] Acicular ferrite formation is well known to be an important phenomenon in regulating grain refinement. Many experiments have been carried out on the characteristics and formation conditions of acicular ferrite in steel.…”
Section: Introductionmentioning
confidence: 99%